2018
DOI: 10.1111/1756-185x.13354
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in Takayasu arteritis

Abstract: Pulmonary hypertension is not infrequent in TA patients and all the potential causes of PH should be carefully evaluated. Patients with severe or treatment-resistant disease are prone to have PH. PAH-specific agents may be effective in patients with group 4 PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
(32 reference statements)
5
19
0
1
Order By: Relevance
“…Additionally, in contrast to the results of Lee et al [23], we did not nd a relationship between PAI and disease activity. This is in accordance with a report from China [24]. The discrepancy between these results could be due to differences in the disease stage of TA because of its gradual onset.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, in contrast to the results of Lee et al [23], we did not nd a relationship between PAI and disease activity. This is in accordance with a report from China [24]. The discrepancy between these results could be due to differences in the disease stage of TA because of its gradual onset.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of PAI has not been fully elucidated. PAI is reported with TAK in 5.7 to 25.93 % (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In this study, the presence of PAI was 14.6 %, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Vessel wall in ammation leads to arterial wall thickening, dilation, stenosis and occlusion. PA involvement (PAI) occurs in 5.7-25.93 % of all cases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). TAK with PAI is occasionally complicated with pulmonary hypertension (PH), resulting in the risk of early mortality (8, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PAI are more prone to develop PH than those without PAI. Sari, et al 12 reported that PH was present in 25.0% of patients with PAI and 7.7% without PAI. In a case review conducted by Toledano, et al 7 , 42.2% of patients with PAI also had PH.…”
Section: Discussionmentioning
confidence: 98%
“…However, the pulmonary circulation is often overlooked in the initial assessment of patients with TA. Pulmonary hypertension (PH) is a major complication in the course of TA-associated PAI [6][7][8][9][10][11][12] . The diagnosis of PH carries a 7-fold higher risk of early mortality in many different clinical conditions 13 .…”
mentioning
confidence: 99%